EMULSI KAYA OMEGA-3 DAN SQUALENEDARI KOMBINASI MINYAK IKAN SARDIN DAN CUCUT - Muhamad Musbah; Rahmi Fitriawati AM; Yeldi S Adel; Muliadin Muliadin (Jurnal Pengolahan Pangan, 2018)
Sardine fish oil contains essential omega-3 fatty acids, EPA (Eikosapentanoat Acid) and DHA (Dokosaheksaenoat Acid) which have an important role for human health. In addition to omega-3 fatty acids there is also a squalen obtained from liver of sharkoils that have considerable benefits to human health as inhibitor cancer, diabetes and endurance. The combination of sardine oil rich omega-3 and squalen from shark oils into commercial emulsified products is underresearch. This research aims to make emulsion formulation fish oils rich of omega-3 and squaleneby treating the guar gum emulsifier concentration. Based on the stability test parameters and droplet / globula size the best emulsion product was produced on a formula with guar gum concentration of 1.1%.